2009
DOI: 10.1007/s12020-009-9226-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors for glucose intolerance in young Korean women with polycystic ovary syndrome

Abstract: Insulin resistance and hyperinsulinemia play important roles in the pathogenesis of polycystic ovary syndrome (PCOS). In addition, some women with PCOS have been shown to have insulin secretory defects and can be predicted to be at an increased risk for glucose intolerance. We performed the present study to determine the prevalence and risk factors for glucose intolerance in Korean women with PCOS. We consecutively recruited 194 women with PCOS diagnosed by American Society for Reproductive Medicine/European S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 29 publications
4
31
0
1
Order By: Relevance
“…In the Finnish Diabetes Prevention study, baseline risk score determined study intervention with participants assigned to written information (baseline risk score [7][8][9][10][11][12][13][14] or active lifestyle intervention (baseline risk score R15) (21). Given significant reductions in progression to DM2 after lifestyle interventions in the diabetes prevention study, these implications are important to consider in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…In the Finnish Diabetes Prevention study, baseline risk score determined study intervention with participants assigned to written information (baseline risk score [7][8][9][10][11][12][13][14] or active lifestyle intervention (baseline risk score R15) (21). Given significant reductions in progression to DM2 after lifestyle interventions in the diabetes prevention study, these implications are important to consider in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PCOS has been associated with obesity, insulin-resistance (IR), and a risk of developing Type 2 diabetes mellitus (T2DM). [6] The metabolic and reproductive abnormalities predispose women to develop infertility and endometrial cancer, necessitating early diagnosis and appropriate treatment. [7]…”
Section: Introductionmentioning
confidence: 99%
“…Women with PCOS have a significantly increased prevalence of IGT and undiagnosed diabetes 3. We previously reported that the prevalence of IGT and/or impaired fasting glucose (IFG) and T2DM was 17.0% and 1.0%, respectively, in young Korean women with PCOS 4. The routine use of an oral glucose tolerance test (OGTT) is recommended for screening for IGT and T2DM in women with PCOS 56.…”
Section: Introductionmentioning
confidence: 99%